Family rivalry and its impact on local democracy: An analysis of political dynasties in Samosir Regency, Indonesia - Setyawibawa, Ruruh Aris; Harahap, R. Hamdani; Amin, Muryanto; Achmad, Nurman (Research Journal in Advanced Humanities, 2024)
Political dynasties in Indonesia often serve as a tool to maintain concentrated power, resulting in a centralized power structure and potential negative impacts on democratization. This research analyzes the dynamics of dynastic politics and family rivalry in the Regional Head Election in Samosir Regency, North Sumatra, Indonesia. Using a qualitative approach, the research method involved document analysis, in-depth interviews with local political figures, and field observations to identify the impact of political dynasties on local democratic processes. The findings show that competition within clans creates political tensions and contributes to shifts in people’s assessment of the quality and legitimacy of leaders. While political dynasties can offer stability, they often reduce transparency and accountability and inhibit public participation. This research highlights the importance of understanding how political dynasties adapt to electoral system changes and their impact on local political dynamics. Recommendations include evaluating public policies to reduce the negative impact of political dynasties, improve accountability, and strengthen public participation in democratic processes. Further research is needed to explore how internal rivalries within political dynasties affect elections and community responses to political change.